PUBLIC SMOKING ISSUE. PRIMARY RESPONSIBILITY: JOHN LYONS, SHARON RANSOME, KAY THOMAS. PUBLIC RELATIONS DIVISION VARIANCE ANALYSIS - LYONS J; RANSOME S; THOMAS K (Tufts Archival Research Center, 2007)
December 1988 Progress Report on Public Smoking Issue. Includes Public Relations Division Variance Analysis for Public Smoking Issue and Scientific Affairs. Highlights substantial work on the Indoor Air Quality (IAQ) issue, including training of new scientific witnesses, new promotional and marketing materials production, and work with the National Energy Management Institute (NEMI) and the Labor Management Committee (LMC), including briefings of labor groups. Discusses Litigation Program, including John Fox's Breakfast Briefings in Seattle and Hawaii, and Phyllis James' attempts to meet with minority bars. Presents work of Corporate/Smoker Assistance Program, focusing on production of media materials and seminars. Indicates Conflict Resolution and Smokers' Rights Groups programs are on indefinite hold.